Sodium aurothiomalate does not block interleukin 1 production in rabbits. - Zurovsky, Y (1988)
Gold salts may attenuate inflammatory processes by inhibiting interleukin 1 production. It is shown that sodium aurothiomalate does not act as an antipyretic after intravenous injection of two pyrogens into rabbits. Consequently, it cannot suppress interleukin 1 production, a conclusion confirmed by an in vitro lymphocyte activating factor assay. Chronic sodium aurothiomalate treatment, however, did depress the blood leucocyte count significantly.